MAQASID SHARIA'S VIEW ON THE SCARCITY OF SUBSIDIZED FERTILIZERS ON THE WELFARE OF FARMERS IN EAST OKU INDONESIA - Meriyati Meriyati; M. Nasyah Agus Saputra; Imamul Arifin; Maya Panorama; Mahmoud Saleh Mubarak Bin Humaid (Profetika: Jurnal Studi Islam, 2023)
In addition to functioning to meet food needs, the agricultural sector also plays an important role, becoming a provider of employment and a source of income for regional communities. Unfortunately, almost every year this sector is faced with a scarcity of subsidized fertilizers and poorly controlled prices. The problem in this East OKU Belitang is the scarcity of subsidized fertilizers and price increases, as well as the purchasing system for both farmer cooperative members and independently, causing hardship for farmers. The method used is qualitative; fertilizer problems continue to occur, starting from a suboptimal planning and supervision system to a lack of realization of the allocation of fertilizer needs by farmers. The two main human needs that I conveyed above are basic needs that must be met to achieve a prosperous life. Although, of course, there are many other needs that humans have.